Laboratory diagnosis of cryptosporidiosis. - Casemore, D P (1985)
Cryptosporidium spp is now widely accepted as a cause of gastroenteritis. Various methods have been applied to detect oocysts in faeces, but the difficulties of discriminating between non-cryptosporidial bodies, acid fast bodies like cryptosporidia, and cryptosporidia remain. A simple examination in two stages, suitable for routine use is described, using auramine phenol and carbol fuchsine for screening and a modified Ziehl-Neelsen staining method for confirmation. A further method, using Jenner and Giemsa stains, is of value for confirmation of identity, especially where fluorescence microscopy is unavailable. A modification of the formol-ether method of concentration is also described. Immunofluorescence and thin section electron microscopy provide definitive identification. Vomiting can be an important clinical feature of gastroenteritis, and the first description of oocysts in vomit is reported. Preliminary findings, after more than two years of study show that Cryptosporidium is an important pathogenic agent in gastroenteritis, confirm the increased incidence in children, and suggest a possible seasonal trend.